Age-specific atrial fibrillation incidence, attributable risk factors and risk of stroke and mortality: results from the MORGAM Consortium - Morseth Bente; Geelhoed Bastiaan; Linneberg Allan; Johansson Lars; Kuulasmaa Kari; Salomaa Veikko; Iacoviello Licia; Costanzo Simona; Söderberg Stefan; Niiranen Teemu J; Vishram-Nielsen Julie KK; Njølstad Inger; et al. (BMJ Publishing Group, 2022)
Background
The main aim was to examine age-specific risk factor associations with incident atrial fibrillation (AF) and their attributable fraction in a large European cohort. Additionally, we aimed to examine risk of stroke and mortality in relation to new-onset AF across age.
Methods
We used individual-level data (n=66 951, 49.1% men, age range 40–98 years at baseline) from five European cohorts of the MOnica Risk, Genetics, Archiving and Monograph Consortium. The participants were followed for incident AF for up to 10 years and the association with modifiable risk factors from the baseline examinations (body mass index (BMI), hypertension, diabetes, daily smoking, alcohol consumption and history of stroke and myocardial infarction (MI)) was examined. Additionally, the participants were followed up for incident stroke and all-cause mortality after new-onset AF.
Results
AF incidence increased from 0.9 per 1000 person-years at baseline age 40–49 years, to 17.7 at baseline age ≥70 years. Multivariable-adjusted Cox models showed that higher BMI, hypertension, high alcohol consumption and a history of stroke or MI were associated with increased risk of AF across age groups (p<0.05). Between 30% and 40% of the AF risk could be attributed to BMI, hypertension and a history of stroke or MI. New-onset AF was associated with a twofold increase in risk of stroke and death at ages≥70 years (p≤0.001).
Conclusion
In this large European cohort aged 40 years and above, risk of AF was largely attributed to BMI, high alcohol consumption and a history MI or stroke from middle age. Thus, preventive measures for AF should target risk factors such as obesity and hypertension from early age and continue throughout life.
Data availability statement
The data are not available in a public repository. Access to the data is restricted by the ethical approvals and the legislation of the European Union and the countries of each MORGAM study. Approval by the Principal Investigator of each cohort study and the MORGAM/BiomarCaRE Steering Group will be required for release of the data. The MORGAM Manual at https://www.thl.fi/publications/morgam/manual/contents.htm gives more information on access to the data.